Evolution of important glucosinolates in three common Brassica vegetables during their processing into vegetable powder and in vitro gastric digestion. Issue 1 (9th January 2020) - Kuljarachanan, Thitima; Fu, Nan; Chiewchan, Naphaporn; Devahastin, Sakamon; Chen, Xiao Dong
Abstract : Evolution of sinigrin, glucoraphanin, glucoerucin and glucobrassicin in Brassica vegetables during processing and in vitro gastric digestion was investigated. Abstract : Evolution of important glucosinolates (GLSs), namely, sinigrin, glucoraphanin, glucoerucin and glucobrassicin, in three commonly consumed Brassica vegetables viz . white cabbage, Chinese cabbage and bok choy during their processing into vegetable powder was investigated. Drying was noted to be a major processing step causing significant losses of GLSs. Interestingly, different GLSs and even the same GLSs in different vegetables showed different thermal stabilities during drying. The stability of GLSs in vegetable powder during in vitro gastric digestion was also studied. Glucoraphanin exhibited the highest stability while glucobrassicin was the most vulnerable GLS under in vitro gastric conditions. White cabbage is found to be a promising material for the production of vegetable powder as it contains high contents of GLSs, especially glucoraphanin and glucoerucin, which are important precursors of anticarcinogenic compounds, namely sulforaphane and erucin. These two GLSs were also noted to be stable during in vitro gastric digestion.